Kilbirnie netmakers' strike, 1913 (1913)
1913 1880-1914 "Kilbirnie netmakers' strike, 1913" [T0182.jpg], 1913 Machines for the manufacture of fishing nets, notably herring drift nets, had been introduced in Kilbirnie in 1900. It was exhausting work as workers operated the machines by jumping on various treadles in their bare feet. The National Federation of Women Workers organiser in Scotland, Kate McLean, set up a branch at the thread mill in Kilbirnie in 1912 and hundreds of women joined within the first year. These workers successfully reported an increase in wages and in 1913 decided to strike in support of non-union net workers demands for a similar increase. The strike lasted 22 weeks and there were frequent skirmishes with the police. With the help of the Scottish Trades Union Congress, who raised £1300 in financial support, the strike was finally settled in September 1913 with an agreement which included union recognition and non-victimisation of strikers.